In this way it was begun to teach, to get the figure of what is known (2014)
Abel Rodriguez tells us how his painting is inscribed within the process of reactualization of the cosmic creation narrated in Nonuya oral history. Such a reactualization is carried out daily, beginning by the night-time teaching of the creator´s words and developing into the day through the labor and sweat of the people who transform those words into figures, giving them material existence by making gardens, houses and bodies of kin gathering at feasts. The paintings of Abel show different moments of these processes.